2009
DOI: 10.1007/s12630-009-9205-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistance et voie de l’inhibition de la production de superoxyde par les neutrophiles induite par isoflurane

Abstract: Background Our previous work has demonstrated that treatment with isoflurane has a preconditioning-like inhibitory effect on superoxide production (SOP) by polymorphonuclear neutrophils. The current objectives were to determine persistency of this effect and to clarify where in the signalling pathway this inhibition of SOP occurred. The latter was accomplished using two receptor-dependent neutrophil agonists, platelet activating factor (PAF) and formyl-methionyl-leucyl-phenylalanine (fMLP), and two receptor-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…However, clinically relevant doses of ISO protect organs (e.g., lung, liver, kidney, and intestine) injury induced by inflammation resulting from endotoxemia or ischemia-reperfusion [4246]. Moreover, 1.4% ISO administration causes prolonged decreases in agonist-induced superoxide production by neutrophils [47]. These conflicting findings possibly stemmed from different pathological states or molecular mechanisms employed by ISO.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinically relevant doses of ISO protect organs (e.g., lung, liver, kidney, and intestine) injury induced by inflammation resulting from endotoxemia or ischemia-reperfusion [4246]. Moreover, 1.4% ISO administration causes prolonged decreases in agonist-induced superoxide production by neutrophils [47]. These conflicting findings possibly stemmed from different pathological states or molecular mechanisms employed by ISO.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, halogenated anaesthetics attenuate the production of ROS by activated PMN (Frohlich et al. 1997; Saad et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…(1997) demonstrated that the volatile anaesthetics halothane, enflurane and sevoflurane inhibited the oxidative response of human neutrophils to fMLP challenge by inhibiting the signal transduction upstream of protein kinase C (PKC), possibly at the level of the calcium‐calmodulin complex. In a concordant study, Saad et al. (2010) used receptor‐dependent and receptor‐independent stimuli to show that isoflurane decreased PMNs respiratory burst by inhibition of the signalling pathway upstream from PKC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, isoflurane can potentially interfere at different levels, such as the central nervous system [9], [10] or the immune system. Indeed, isoflurane has anti-inflammatory properties which can be sources of interferences in studies concerning inflammation [11], [12], [13], [14], [15], [16], [17], [18]. Moreover, the use of isoflurane has not yet been studied in a VNS rat model.…”
Section: Introductionmentioning
confidence: 99%